An experimental investigation on longitudinal shear of composite slab based on eurocode 4 - Mok, Eugene Kai Boon. (2012)
There are generally four modes of failure for Composite Slabs – Longitudinal shear (shear bond) failure, Vertical shear failure, Flexural failure and Punching shear failure. Of the four modes, longitudinal failure is considered to be the governing criteria in the design of composite slabs as it yielded the lowest load that caused the composite slab to fail. In this project, verification of the longitudinal shear as the lowest failure load and distinct mode of failure in composite slab will be shown (in conjunction with project ST48AB). Interface between the concrete and the steel profiled sheet (metal decking) was studied with respect to BS EN 1994-1-1:2004 (Eurocode 4). Data analysis based on both Eurocode 4 and BS5950–4:1994 (BS5950) will be compared.